Pelvic Organ Prolapse – General Overview and Latest Therapy Possibilities - Wojtas, Aneta Klaudia; Cygnarowicz, Aleksandra; Sacher, Karolina; Zabojska, Krystyna; Korotko, Urszula; Mandziuk, Aneta; Witowska, Kinga; Turemka, Mariola; Biskupski, Mikolaj; Hosseinnejad, Negar (Quality in Sport, 2024)
Pelvic organ prolapse (POP) is a very common health problem, which affects increasing number of women. The etiology involves multiple factors, especially ageing or increased abdominal pressure. It refers to the downward displacement of the pelvic organs and its protrusion. This condition can significantly affect the quality of life, causing urinary and fecal incontinence, sexual dysfunctions and self-consciousness. The examination includes both physical and imaging studies. Patients can be offered an observations, pessaries and surgeries, such as obliterative and reconstructive surgeries. A literature for this review was gathered on PubMed and Google Scholar, using keyword “pelvic organ prolapse”, combined with “epidemiology”, “pathophysiology”, “risk factors”, “symptoms”, “complications”, “treatment”, “surgery” and “pessaries”.